Relationships between welfare and reproductive performance in French dairy herds. (June 2019) - Grimard, B.; de Boyer des Roches, A.; Coignard, M.; Lehébel, A.; Chuiton, A.; Mounier, L.; Veissier, I.; Guatteo, R.; Bareille, N.
Highlights: There is a social demand for improved animal welfare in food producing. Animal welfare can be estimated by the Welfare Quality Protocol in dairy cows. Reproductive performance is a componment of productivity in dairy cows. Calving to first service interval and calving rate were related to welfare. Improved welfare was related to higher reproductive performance. Abstract: This study aimed to investigate the relationship between cow reproductive performance and welfare evaluated at the herd level using the Welfare Quality protocol. The 11 criteria, four principles (good feeding, good housing, good health and appropriate behavior, scale 0–100) and overall welfare category (excellent/enhanced/acceptable/not classified = poor welfare) were included as risk factors for calving to first service interval (CFSI) and calving rate (CR). The confounding factors cow breed, parity, season of calving and AI, calving to AI interval, rank of AI (1–3) and milk production were taken into account. The sample included 3951 AIs (2172 AI1, 1182 AI2, 597 AI3) in 124 French commercial dairy herds. Median CFSI was shorter for the cows bred in herds with a higher overall welfare category (median 75 and 76 days in enhanced and acceptable herds vs. 86 in poor welfare ones, P  =  0.02). The scores for absence of injuries and expression of social behavior tended to be associated with CFSI ( P  <  0.10). Calving rate (34.5%) was not related to the overall welfare category. However, CR was positively related to the good housing score and a positive trend was observed with the scores for absence of prolonged hunger and absence of injuries. In conclusion, this study confirms a positive relationship between CFSI and welfare in dairy cows with no explicit links with specific aspects of animal welfare.